Optimal procurement with quality concerns - Giuseppe Lopomo; Nicola Persico; Alessandro T. Villa (Federal Reserve Bank of Chicago, 2022)
Adverse selection in procurement arises when low-cost bidders are also lowquality suppliers. We propose a mechanism called LoLA which, under some conditions, is the best incentive-compatible mechanism for maximizing either the seller's or the social surplus in the presence of adverse selection. The LoLA features a floor (or minimum) price, and a reserve (or maximum) price. Conveniently, the LoLA has a dominant strategy equilibrium that, under mild regularity conditions, is unique. We perform a counterfactual experiment on Italian government procurement auctions: we compute the gain that the government could have made, had it used the optimal mechanism (which happens to be a LoLA), relative to a first-price auction, which is the format the government actually used. Finally, we provide software applications for computing the optimal procurement mechanism.
Keywords: 330; Procurement Auctions; Mechanism Design; Auctions; Asymmetric and Private Information; Mechanism Design